Cortisol Regulation in the Metabolic Syndrome. A Novel Therapeutic Approach - Marin, Per; S. Birketvedt, Grethe (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2010)
The metabolic syndrome is characterized by visceral obesity, insulin resistance, Type 2 diabetes, dyslipidemia and hypertension. All these disturbances are also typically associated with cortisol hyperactivity, such as Cushing s syndrome. Therefore, it seems worthwhile to consider increased cortisol activity in the metabolic syndrome, despite normal circulating levels, to be an important pathogenetic mechanism. Thirty women, 49-65 yr old, with visceral obesity, insulin resistance and Type 2 diabetes were treated with ketoconazole 400 mg daily, in order to down-regulate cortisol activity, in a 3-month randomized, double-blind, placebo-controlled trial. The insulin resistance was evaluated with an euglycemic, hyperinsulinemic glucose clamp. Body fat was assessed from total body potassium. During the study, insulin resistance improved in the ketoconazole-treated group as compared to the placebo-treated one (p<0.05). Total cholesterol (p<0.05), fasting glucose (p<0.05) and HbA1c (p<0.05) levels decreased, whereas serum triglyceride levels and insulin concentrations were unaffected by the ketoconazole treatment. Systolic (p<0.05) and diastolic (p<0.05) blood pressure decreased in the ketoconazole treated group. Body fat was unchanged in both groups. Furthermore, liver AST (p<0.05), ALT (p<0.05) and ALP (p<0.05) decreased in response to ketoconazole treatment. This study has demonstrated that a down-regulation of cortisol secretion can favorably affect most of the multiple risk factors associated with the metabolic syndrome. This includes improvement in insulin resistance, glucose homeostasis, total cholesterol, blood pressure and hepatic steatosis.
Keywords: glucocorticoid receptors